The throne, the lamb and the dragon a readers guide to the Book of Revelation - Spilsbury, Paul, 1966- (Downers Grove, IL IVP, 2002)
Includes bibliographicla references and index.
Keywords: Bible. N.T. Revelation -- criticism, interpretation, etc